Electroacupuncture Alleviates Bladder Overactivity via Inhabiting Bladder P2X3 Receptor. (17th March 2020) - Feng, Qi-fan; Zhang, An-dong; Xing, Man; Wang, Xi; Ming, Shu-ren; Chen, Yue-lai
Abstract : Electroacupuncture (EA) has been widely applied for overactive bladder, but the mechanism of its action remains to be clarified. This study was aimed to investigate EA regulating the effect of purinergic signaling in the OAB of rats. Electroacupuncture (continuous wave, 30 Hz, 1 mA) was applied to stimulate the Ciliao point (BL32) and the Huiyang point (BL35) of rats. Results showed that when the P2X3 receptor in bladder peripheral level and the spinal cord central level was involved in the bladder micturition reflex of the afferent signaling, intravenous administration P2X3 antagonist AF-353 can significantly inhibit urination in naive rats and OAB of rats and increase bladder volume and micturition pressure. EA stimulation alleviated bladder overactivity significantly and after the P2X3 receptor was blocked, the EA effect was weakened. EA stimulation can effectively reduce the P2X3 mRNA and protein expression in OAB of rats, spinal cord (L6-S1), and DRG (L6-S1) and can significantly reduce the number of positive P2X3 cells in OAB of rats, spinal cord (L6-S1), and DRG (L6-S1). These findings suggest that EA stimulation could alleviate bladder overactivity, and the function is closely related to the inhabited P2X3 receptor in the bladder.